VD_FINDINFO HC / 2012 / 588 vom 11. September 2012 - VD Tribunal cantonal (2012)
MAXIME INQUISITOIRE, CONSTATATION DES FAITS, OBLIGATION D'ENTRETIEN, CONJOINT, REVENU HYPOTHÉTIQUE | 163 CC, 176 al. 1 ch. 1 CC, 272 CPC (CH), 317 al. 1 CPC (CH)